COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA BELANJA PASAR SENI SUKAWATI KABUPATEN GIANYAR - Indriani, Ni Kadek; Yasintha, Putu Nomy; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2021)
Sukawati art market is one of the traditional art markets that must be preserved. This research aims the process of Collaborative Governance in the Development of Shopping Objects Sukawati Art Market Gianyar Regency. There are still problems in the collaboration process, namely the lack of government and human resources roles are inadequate. The research method used in this study is descriptive qualitative. The analysis uses collaboration process indicators according to Ansell and Gash as well as the Collaboration Success Measure according to Deseve. The result shows that the collaboration between the government and the private sector went well, but the collaboration between businesses with the Department of Industry and Trade gianyar regency and PT. Putera Jaya Andalan is still reaping problems. Keywords: Collaborative Governance, Sukawati Art Market, Tourism Object Developmen